Development and validation of an LC-MS/MS method for highly concentrated tacrolimus and cyclosporine samples prepared from pharmaceutical products to assess drug loss from feeding tubes - Yi Xiao; Mari Ishak Gabra; Edward Leung (Journal of Mass Spectrometry and Advances in the Clinical Lab)
Introduction: Tacrolimus and cyclosporine are common immunosuppressants utilized post-organ transplantation to manage allograft rejection. Both have narrow therapeutic indices and are frequently measured to support dose adjustments. Although nasogastric tubes are commonly used to provide nutritional support and serve as a route for immunosuppressant administration, they were never validated for such purposes. Objective: To develop and validate a liquid chromatography – tandem mass spectrometry (LC-MS/MS) method for highly concentrated tacrolimus and cyclosporine samples prepared from pharmaceutical products to support the validation of feeding tube administration of these immunosuppressants. Methods: The method involved stepwise dilutions with dimethyl sulfoxide before analysis using online sample preparation and LC-MS/MS. It was validated in a CLIA-certified clinical laboratory that measures immunosuppressants by LC-MS/MS and is designed to support clinical studies evaluating drug loss from feeding tubes. Results: The method was linear between 6.8 µg/mL and 75 µg/mL for tacrolimus, and between 0.9 mg/mL and 10 mg/mL for cyclosporine, with r2 > 0.99 and total precision <5 % at all QC levels. The method demonstrated good recovery using cyclosporine Certified Reference Material, tacrolimus European Pharmacopeia Reference Standard, and prepared pharmaceutical products. Minimal matrix effects were observed. Conclusion: An analytical method was developed and validated for in vitro studies with simulated administration of tacrolimus or cyclosporine to assess loss during drug administration using feeding tubes.